2018
DOI: 10.1111/grs.12219
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen addition stimulated compensatory growth responses to clipping defoliation in a Northern Tibetan alpine meadow

Abstract: Grazing and clipping defoliation are the most important human disturbances in natural grasslands. Compensatory growth is a common response to clipping defoliation, which is of great significance for forage production and livestock husbandry development. However, how clipping intensity affects plant compensatory growth and how nitrogen (N) addition regulates this response in alpine ecosystems are still unclear. A manipulative experiment including two clipping intensities (light and heavy) crossed with N additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This is because, conversely, these abiotic factors will probably have significant effects on the soil carbon cycle of such grasslands (Han et al, 2012; Hopkins & Del Prado, 2007). Many studies showed how different mowing frequencies applied to seminatural grasslands affect aboveground biomass production (Bernhardt‐Römermann et al, 2011; D'Ottavio & Ziliotto, 2003; Rose et al, 2012; Zong & Shi, 2019) that, despite variations in management, is positively correlated to soil respiration (Raich & Tufekcioglu, 2000). Other studies also show how the below ground biomass in grasslands affects soil CO 2 emission depending on several parameters (e.g., roots diameter, age, N concentration) (Bahn et al, 2006; Koncz et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because, conversely, these abiotic factors will probably have significant effects on the soil carbon cycle of such grasslands (Han et al, 2012; Hopkins & Del Prado, 2007). Many studies showed how different mowing frequencies applied to seminatural grasslands affect aboveground biomass production (Bernhardt‐Römermann et al, 2011; D'Ottavio & Ziliotto, 2003; Rose et al, 2012; Zong & Shi, 2019) that, despite variations in management, is positively correlated to soil respiration (Raich & Tufekcioglu, 2000). Other studies also show how the below ground biomass in grasslands affects soil CO 2 emission depending on several parameters (e.g., roots diameter, age, N concentration) (Bahn et al, 2006; Koncz et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, different studies have suggested that the response in terms of soil respiration of N‐fertilized grasslands subjected to different herbage removal frequencies depends on the actions and interactions of other direct factors (e.g., mowing effects on plant roots) and indirect factors (e.g., drivers of soil respiration: soil temperature, water content). For example, Zong and Shi (2019) reported that a higher mowing frequency for semiarid N‐fertilized grasslands might not result in continuous increases in plant compensatory growth. Interruptions to, or slowdowns of, plant compensatory growth can reduce the contributions of the root component to total soil respiration (Wei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For perennial plant species, the interaction between above and belowground organs are critical to both individual growth in the current growing season and population persistence in the next year ( Briske and Richards, 1995 ; Zong and Shi, 2019 ); thus, this may be the determining factor for the temporal stability of the whole ecosystem ( Zhang et al, 2017 ; Xu et al, 2020 ). Two-rounds of shoot defoliation directly reduced the remaining and accumulated biomass by 64.66 and 57.51%, and indirectly reduced the root biomass by 60.11% ( Figure 1 and Supplementary Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%